ANALISIS JENIS BUSI DAN JENIS BAHAN BAKAR TERHADAP DAYA DAN TORSI PADA MOTOR 125CC INJEKSI: ANALYSIS OF SPARK PLUG TYPE AND FUEL TYPE ON POWER AND TORQUE IN 125CC INJECTION MOTORCYCLE - Aditya; Purwoko; Cahyono, Hiding; Setiawan, Deny; Rojikin, Setyo (Jurnal Teknik Mesin, 2023)
Spark plugs and gasoline are two essential elements in motor vehicles, whether they are two-wheeled, three-wheeled, or four-wheeled. Spark plugs come in various types, just like gasoline, which has many different variants with varying quality levels. The purpose of this research is to determine the differences in power output and torque when using standard spark plugs, platinum spark plugs, and iridium spark plugs, along with RON 90 and RON 92 gasoline from PT P and PT B in a 125cc fuel-injected motor. Data collection for this research was conducted using the observation method. In the test results, there were differences in Power and Torque. When using Pertalite fuel (RON 90) with platinum spark plugs, the power output was 10.03 HP (8000 RPM), and the torque was 10.37 Nm (6000 RPM). On the other hand, when using BP 90 fuel (RON 90) with iridium spark plugs, the power output was 10.53 HP (8000 RPM), and the torque was 10.50 Nm (6000 RPM).